The effects of total lymphocyte deficiency on the extent of atherosclerosis in apolipoprotein E-/- mice. - Daugherty, A (1997)
Activated T lymphocytes are present in human atherosclerotic lesions and autoantibodies to antigens within lesions have been detected in serum, but the roles of the cellular and humoral immune systems in atherogenesis have not been determined. The effect of total lymphocyte deficiency on atherogenesis was investigated by crossing apo E-deficient mice (which develop atherosclerosis resembling human disease) with mice deficient in RAG2 (which is required for normal B and T lymphocyte development). Mice were placed on a fat- and cholesterol-enriched diet for 12 wk. RAG2-deficient mice had no serum autoantibodies, in contrast to the high titers in RAG2+/- littermates. There were no T lymphocytes and a markedly reduced number of MHC class II-positive macrophages in atherosclerotic lesions of RAG2-deficient mice. Despite these differences, RAG2-deficient mice developed atherosclerosis similar in extent to that in immunocompetent littermates, based on quantification by two independent methods. In conclusion, the absence of autoantibodies and T lymphocytes did not influence the extent of aortic atherosclerotic lesions in apo E-deficient mice.